LIGHT elevation enhances immune eradication of colon cancer metastases - Qiao, Guilin (Cancer Res, 2017)
The majority of colon cancer patients will develop advanced disease with the liver being the most common site of metastatic disease. Patients with increased numbers of tumor-infiltrating lymphocytes in primary colon tumors and liver metastases have improved outcomes. However, the molecular factors which could empower anti-tumor immune responses in this setting remained to be elucidated. We reported that the immunostimulatory cytokine LIGHT (TNFSF14) in the microenvironment of colon cancer metastases associates with improved patient survival, and here we demonstrate in an immunocompetent murine model that colon tumors expressing LIGHT stimulate lymphocyte proliferation and tumor-cell specific anti-tumor immune responses. In this model, increasing LIGHT expression in the microenvironment of either primary tumors or liver metastases triggered regression of established tumors and slowed the growth of liver metastases, driven by cytotoxic T-lymphocyte mediated anti-tumor immunity. These responses corresponded with significant increases in tumor-infiltrating lymphocytes and increased expression of lymphocyte-homing signals in the metastatic tumors. Further, we demonstrated evidence of durable tumor-specific anti-tumor immunity. In conclusion, increasing LIGHT expression increased T-cell proliferation, activation, and infiltration, resulting in enhanced tumor-specific immune-mediated tumor regressions in primary tumors and colorectal liver metastases. Mechanisms to increase LIGHT in the colon cancer microenvironment warrant further investigation and hold promise as an immunotherapeutic strategy.